Association of Alcohol Intake With Hypertension in Type 2 Diabetes Mellitus: The ACCORD Trial - Jonathan J. Mayl; Charles A. German; Alain G. Bertoni; Bharathi Upadhya; Prashant D. Bhave; Joseph Yeboah; Matthew J. Singleton (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Heavy alcohol consumption has a well‐established association with hypertension. However, doubt persists whether moderate alcohol consumption has a similar link. This relationship is not well‐studied in patients with diabetes mellitus. We aimed to describe the association of alcohol consumption with prevalent hypertension in participants in the ACCORD (Action to Control Cardiovascular Risk in Diabetes) trial. Methods and Results Alcohol consumption was categorized as none, light (1–7 drinks/week), moderate (8–14 drinks/week), and heavy (≥15 drinks/week). Blood pressure was categorized using American College of Cardiology/American Heart Association guidelines as normal, elevated blood pressure, stage 1 hypertension, and stage 2 hypertension. Multivariable logistic regression was used to explore the association between alcohol consumption and prevalent hypertension. A total of 10 200 eligible participants were analyzed. Light alcohol consumption was not associated with elevated blood pressure or any stage hypertension. Moderate alcohol consumption was associated with elevated blood pressure, stage 1, and stage 2 hypertension (odds ratio [OR], 1.79; 95% CI, 1.04–3.11, P=0.03; OR, 1.66; 95% CI, 1.05–2.60, P=0.03; and OR, 1.62; 95% CI, 1.03–2.54, P=0.03, respectively). Heavy alcohol consumption was associated with elevated blood pressure, stage 1, and stage 2 hypertension (OR, 1.91; 95% CI, 1.17–3.12, P=0.01; OR, 2.49; 95% CI, 1.03–6.17, P=0.03; and OR, 3.04; 95% CI, 1.28–7.22, P=0.01, respectively). Conclusions Despite prior research, our findings show moderate alcohol consumption is associated with hypertension in patients with type 2 diabetes mellitus and elevated cardiovascular risk. We also note a dose‐risk relationship with the amount of alcohol consumed and the degree of hypertension.